Citizen Charter Implementation at Soko Community Health Center, Tuban Regency - Taufiq, Ahmad; Purnomo, Joko Hadi (IDFoS Indonesia, 2021)
This research aimed to describe how the implementation of the citizen charter at Soko Community Health Center, the role and behavior of the service apparatus at Soko Community Health Center after the signing of the service notice, as well as the completeness of the supporting facilities and infrastructure as promised in the service at Soko Community Health Center. Qualitative research method was used in this research. The results showed that the types of services provided by Soko Community Health Center were generally well implemented according to the citizen charter. The service promises provided included the service types, the suitability between the service type and service personnel, services for TB patients, immunization services, leprosy establishment services, maternity and emergency services, inpatient services, administrative services for referral letters and health letters. However, there were several things noted for improvement, for example related to services at Maternal dan Child Health (MCH) Poly, the timeliness of services, public ignorance about special services for TB patients (83%), immunization (56.3%), services for leprosy patients (91.7%), delivery services emergency department in which 83.3% stated that it was appropriate, only 16.7% of respondents surveyed said they did not know, as well as several other records found in the field. Keywords: Implementation, Citizen Charter, Community Health Center